Portlandite consumption by red ceramic waste due to alkali activation reaction - Macioski, Gustavo; Soto, Nicolle Talyta Arriagada; Medeiros, Marcelo Henrique Farias de; Hoppe Filho, Juarez; Araújo, Marcia Silva de; Cerri, José Alberto (Ambiente Construído, 2020)
Red ceramics, due to the low compressive strength and high porosity, make it difficult to use it as an artificial aggregate in the production of mortars and concretes. However, since it has a silicon-rich composition, the ceramic material from blocks and tiles has been studied as a possible supplementary cementitious material in concrete and also as a raw material in alkali-activated binders. This paper aims to evaluate the content of calcium hydroxide (portlandite) fixed in the alkali activation reaction and the microstructure of red clay waste from construction and demolition waste (CDW) and hydrated lime mixtures, varying the atomic ratio between the silicon and the calcium. The results indicated that higher availability of lime is directly related to the content of hydrated compounds and its porosity. The increase in the silicon/calcium ratio resulted in a reduction of available lime content by 40% and an increase, in volume, of micropores by 7%.